The potential reduction of carbon dioxide (CO2) emissions from gas flaring in Nigeria’s oil and gas industry through alternative productive use - Otene IJJ; Murray PE; Enongene KE (MDPI)
Globally, climate change and its adverse effects on the human population and the environment has necessitated significant research on the sustainable use of natural resources. Gas flaring in Nigeria’s oil and gas industry causes environmental and health hazards and to a large extent, culminates in yearly loss of the Nation’s revenue. The aim of the study is to highlight the potentials of converting flared gas from the Nigerian oil and gas industry to compressed natural gas (CNG) which could be an alternative fuel for the 220 Lagos Bus Rapid Transit (BRT-Lite) while reducing CO2 emissions. In addition, the study provided an overview of gas flaring in the oil and gas industry and energy utilisation in some selected sectors in the country. The Long-range Energy Alternative Planning System (LEAP) software was employed to model the energy demand and carbon dioxide emissions from the BRT-Lite by creating a current scenario and projections to the year 2030. The use of CNG as an alternative fuel for Lagos BRT-Lite will significantly reduce CO2 emissions in Nigeria’s oil and gas industry. Other utilization options for flared gas from this industry includes: Liquefied Natural Gas (LNG), Liquefied Petroleum Gas (LPG), and power generation
Keywords: Nigeria; greenhouse gas; flaring; alternative; industry; 0502 Environmental Science and Management